Polityka językowa w układzie transgranicznym (Polska, Litwa, Białoruś) - Zaniewski, Jan; Nizhneva, Natallia; Nizhneva-Ksenofontova, Nadzeya; Ivanauskas, Karolis; Trancygier-Koczuk, Zofia (Scripta Neophilologica Posnaniensia, 2018)
Polityka językowa w układzie transgranicznym (Polska, Litwa, Białoruś)